Effectiveness of Propranolol in treatment of Cutaneous Vascular Malformations (Boletin Médico de Postgrado, 2020)
A quasi-experimental study of time series was carried out to evaluate the effectiveness of propranolol in the treatment of cutaneous vascular malformations in 48 patients attending the Dermatology Service of the Hospital Central Universitario Dr. Antonio Maria Pineda during the period February - July 2018. The results show that there are statistically significant differences (p
Keywords: propranolol; vascular malformations; clinical